The gray scale value of ear tissues undergoing volume-rendering high-resolution cone-beam computed tomography. Issue 5 (October 2018) - Komori, Masahiro; Miuchi, Shinya; Hyodo, Jun; Kobayashi, Taisuke; Hyodo, Masamitsu
Abstract: Objective: When the thresholds for VR reconstruction from multi-slice CT images are changed, problems develop when assessing pathologies in the absence of standardized thresholds. The advantages of CBCT include lower radiation exposure compared with other techniques and better visualization of small ear structures. However, a disadvantage is that the scanner provides unstandardized gray scale values, thus not CT numbers (Hounsfield units, HU). Methods: We analyzed 88 sets of volume data obtained from temporal bones. The gray scale values were measured in aerated areas (two sites), along the ossicular chain (four sites) and in a bone area (one site) in the external and middle ears, and in soft tissue areas (five sites) and bone areas (two sites) in the inner ear. Results: The standard male and female gray scale values were 2448–2970 and 2585–3091 for the aerated areas, 3248–4945 and 3359–5223 for the ossicular chains, 3368–4109 and 3371–4147 for soft tissues, and 4790–5776 and 5044–5959 for bone, respectively. Sex significantly affected the values ( p < 0.05). Significant differences between aerated areas and ossicular chains, and between soft tissues and bone, were evident (all p < 0.0001). Conclusion: Volume-rendering (VR) images obtained by cone-beam computed tomography (CBCT) can be standardized simply by using fixed thresholds.